2016
DOI: 10.1038/srep23797
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Telemonitoring in Patients with Chronic Obstructive Pulmonary Disease in Taiwan-A Randomized Controlled Trial

Abstract: Chronic obstructive pulmonary disease (COPD) is the leading cause of death worldwide, and poses a substantial economic and social burden. Telemonitoring has been proposed as a solution to this growing problem, but its impact on patient outcome is equivocal. This randomized controlled trial aimed to investigate effectiveness of telemonitoring in improving COPD patient outcome. In total, 106 subjects were randomly assigned to the telemonitoring (n = 53) or usual care (n = 53) group. During the two months followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 25 publications
0
101
0
2
Order By: Relevance
“…There are only few randomized controlled trials (RCTs) investigating THC for COPD and even less investigating HRQoL. [16][17][18][19][20][21][22][23] A study from the UK over 12 months found 20 It is important to mention that the THC interventions differed considerably between these studies. The "reaction interval" varied daily, weekly, every 2 weeks and monthly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are only few randomized controlled trials (RCTs) investigating THC for COPD and even less investigating HRQoL. [16][17][18][19][20][21][22][23] A study from the UK over 12 months found 20 It is important to mention that the THC interventions differed considerably between these studies. The "reaction interval" varied daily, weekly, every 2 weeks and monthly.…”
mentioning
confidence: 99%
“…Further, the kind of intervention was very heterogeneous and could consist of measuring heart rate, physical activity, temperature and/or oxygen saturation, online questionnaires based on symptoms, web-based exercising, selfmanagement instructions or spirometry. [16][17][18][19][20][21][22][23] To the best of our knowledge, the CAT has never been assessed as an endpoint for HRQoL in an RCT investigating THC for COPD, despite being recommended as a first-line tool in the assessment of COPD by the GOLD. 1 The fact that the CAT was improved or stable in nearly two-thirds of COPD patients in our THC cohort is promising and could indicate the potential of our proposed THC procedure to significantly improve HRQoL.…”
mentioning
confidence: 99%
“…A care system for chronic diseases has been well established in Taiwan, including telemonitoring in patients with COPD [70]. Lee et al found that the NHI program is associated with substantial reductions in deaths from infections such as pneumonia [71].…”
Section: Strengthmentioning
confidence: 99%
“…Koff et al [39] specified thresholds of 90% and 88%, Ho et al [40] on 92% and 90% and Colantonio et al [41] made the distinction between breathing room air (thresholds of 92% and 90%) and breathing O 2 (thresholds of 93%, 90% and 80%). Three studies that applied individual thresholds did not specify the method for determining the threshold values [42][43][44].…”
Section: Spo 2 Alerts Leading To Immediate Actionmentioning
confidence: 99%